Single‐Step‐Lithography Micro‐Stepper Based on Frictional Contact and Chiral Metamaterial. Issue 28 (16th June 2022) - Tan, Xiaojun; Martínez, Julio Andrés Iglesias; Ulliac, Gwenn; Wang, Bing; Wu, Linzhi; Moughames, Johnny; Raschetti, Marina; Laude, Vincent; Kadic, Muamer
Abstract: Stepper motors and actuators are among the main constituents of control motion devices. They are complex multibody systems with rather large overall volume due to their multifunctional parts and elaborate technological assembly processes. Miniaturization of individual parts is still posing assembly problems. In this paper, a single‐step lithography process to fabricate a micro‐stepper engine with an accurate micrometric rotation axis and an overall sub‐millimeter size is demonstrated. The device is based on the frictional contacts and chiral metamaterials to get rid of the dependence on the accuracy of parts. The functional aspects of fabricated samples are discussed for many rotation cycles and for different frictional surfaces. Abstract : Herein, a single‐step lithography process to fabricate a micro‐stepper engine with an accurate micrometric rotation axis and an overall sub‐millimeter size is demonstrated. The device is based on the frictional contacts and chiral metamaterials to get rid of the dependence on the accuracy of parts. The functional aspects of fabricated samples are discussed for many rotation cycles and for different frictional surfaces.